Legal Protection of Banks for the Cancellation of Land Certificates Due to Overlapping which are Being Breaked with Guarantee Rights - Rolib Sitorus; Leonita (PT FORMOSA CENDEKIA GLOBAL, 2023)
The provision of credit by banks should receive legal protection for both creditors and debtors. One of the conditions for granting credit is the existence of a guarantee that functions to provide a sense of security for creditors against returning credit funds in the event of default or default. The problem in this study is the cancellation of property rights certificates burdened with mortgage rights due to overlapping. The protection given to banks in the event of cancellation of collateral objects in this writing is carried out by collecting library materials and also interviews with empirical normative methods. Empirical normative legal research is research conducted by examining literature and laws and regulations related to problems and information obtained based on interview results. The results of this research are expected to be useful and useful for the development of legal science, especially Civil Law, as well as the fields of Banking Law, Guarantee Law, and Agrarian Law. This research is expected to be used as a source of knowledge, especially how to protect banks in the event of cancellation of collateral objects and the settlement mechanism and preventive efforts made by the Land Agency of the City of South Tangerang to prevent overlapping certificate problems